The Methodology for Photovoltaic Plant Modeling with RETScreen Software application - Jamel, Fábio Castro; Nascimento, Manoel Henrique Reis (International Journal for Innovation Education and Research, 2022)
In today’s world, the search for new energy generation alternatives is increasing and being far from large metropolitan centers is an aggravating factor for the socioeconomic development of municipalities. In addition to the difficulty and high costs of keeping a city in proper working order, the quality of service provided by electricity concessionaires has low efficiency and high consumption of fossil fuels. In order to contribute to a solution, this work aims to present an alternative developed using the RETScreen Software, through the design of a photovoltaic plant, to meet the energy demands of the municipalities in the state of Amazonas. Through the research, we sought to understand and present the particularities of each proposed chapter and, through computer simulation, to develop a renewable source plant to supply the demand of the municipality of São Gabriel da Cachoeira-AM. Two possibilities of application of the result can be analyzed, where the fulfillment of the demand was carried out in a total and partial way and, with that, obtain satisfactory results such as the reduction of 50% of the consumption of fossil fuel, reduction of 25% to 50 % of emission of polluting gases and to present the potential that the generation of photovoltaic energy has for the Amazon region.